The role of logistics in economic growth and global competitiveness - Filip Ž. Bugarčić; Vladimir Mićić; Nenad Stanišić (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2023)
There is a rising demand to find new patterns for economic growth and development, and improving competitiveness, where the role of logistics should be considered in more detail. The main purpose of the article is to examine and compare the effects of countries’ logistics performance in EU, BRICS, and ASEAN, and to test the role of individual logistics components. The research method is based on panel data using fixed effects regressions for the period 2007-2018. The results confirm the positive impact of logistics on economic growth and competitiveness in the total sample and EU countries, while logistics contributes to rising competitiveness in BRICS countries. Individual contributions of LPI components were also identified, presenting the importance of sub-indices for economic growth and national competitiveness. The research implications emphasize the role of logistics as a factor of economic growth and development and highlight its potential in rising national competitiveness. The main contribution is new evidence on the effects of logistics at the level of selected groups of countries, which highlights the importance of this sector and provides recommendations for economic policymakers.